Oral Lichen Planus and Lichenoid Lesions in Sjogren's Syndrome Patients: A Prospective Study - Raouaa Belkacem Chebil; Yassine Oueslati; Marwa Marzouk; Fatma Ben Fredj; Lamia Oualha; Nabiha Douki (Hindawi Limited, 2019)
Objective. The aim of this study was to investigate the prevalence and characteristics of oral lichen planus (OLP) and oral lichenoid lesions (OLL) in Sjogren's syndrome (SS) patients. Patients and Methods. A prospective clinical study was conducted at the Department of Oral Medicine and Oral Surgery in Sahloul Hospital, Sousse, from January 2012 to June 2018. The patients involved in this study were diagnosed with Sjogren's syndrome according to the AECG (American-European consensus group) diagnostic criteria. Among these patients, we searched for those affected by OLP or OLL as determined by the WHO (World Health Organisation) classification of 2003. Clinical variables such as age, sex, medical conditions and medications, type of SS (primary or secondary), clinical form of OLP, and treatment were analyzed. The assessment of the results was performed using SPSS software. Results. We evaluated 30 patients (27 females and 3 males) diagnosed with SS (24 had primary SS) with a mean age of 55 years and 11 months (±11,714). Overall, 9 patients had oral lesions (30%). Two patients had OLP associated with secondary SS (25%). Primary Sjogren's syndrome patients had 6 OLP lesions and one erythematous lichenoid lesion. OLP was erosive in eight patients, among them two had vulvo-vaginal-gingival syndrome. OLP lesions showed improvement in symptoms after topical or general corticosteroids treatment, while OLL showed improvement only under antibiotic treatment. Conclusion. The results of our analysis suggest that patients with SS have 30% prevalence of OLP and OLL. This possible association shows the importance of screening for oral dryness in patients with OLP or OLL. Treatment includes topical or general corticosteroids for erosive forms associated or not with topical antifungal treatment to treat or prevent oral candidiasis.